Non-Invasive Detection of Fetal Vascular Endothelial Function in Gestational Diabetes Mellitus - Chen, Yunyu; Huang, Danping; Liu, Jinrong; Zeng, Fangling; Tang, Guoyi; Lei, Wenjia; Wang, Haiyu; Jiang, Yanmin; Shentu, Weihui; Wang, Hongying (Frontiers in Endocrinology, 2021)
Objectives: Endothelial dysfunction in the fetuses of women with gestational diabetes mellitus (GDM) is associated with their subsequent cardiovascular events. Prenatal assessment of endothelial function in fetuses exposed to intrauterine hyperglycemic environment remains challenging. The aim of this study was to assess the fetal vascular endothelial function in GDM patients using color M-mode derived aortic propagation velocity (APV) and evaluate the correlation of APV with endothelial function biomarkers. Methods: This observational cross-sectional study included 31 gestational diabetic mothers and 30 healthy pregnant mothers from August 2019 to January 2020. Clinical data were compared between the groups. Fetal APV was measured using color M-mode echocardiography at late gestation. Concentrations of endothelial biomarkers including von Willebrand Factor (vWF), vascular endothelial-cadherin and endothelin-1 in umbilical cord serum were assessed. Measurements between diabetic group and controls were compared. Results: vWF was the only endothelial functional marker that differed between the two groups. Fetus in the GDM group had significantly lower APV levels and higher vWF levels compared with the healthy controls (P < 0.05). There was a moderate but significant correlation between APV and vWF (r = −0.58, P < 0.05). There were no associations between APV and ventricular wall thickness or umbilical artery pulsatility index. Conclusions: Color M-mode propagation velocity of aorta is a non-invasive, practical method that correlates well with GDM and fetal endothelial function. This novel metric could contribute to recognizing early vascular functional alterations and hence represents a potential strategy for early risk factor surveillance and risk modification.